Alternative routes to teacher professional identity: Exploring the conflated sub-identities of Teach For America corps members - Matthew A. M. Thomas; Nicole Mockler (Arizona State University, 2018)
Research on the development of professional identity for teachers who enter the profession through alternative routes is still in its infancy. In contrast to their peers who complete traditional initial teacher education programs, these teachers are exposed to different conditions and constraints that produce a range of sub-identities previously unidentified in the literature. This paper draws on interviews with 27 teachers who entered teaching through Teach For America and wrestled with these sub-identities as they considered their emerging professional identity. We argue that these sub-identities point to structural challenges embedded within Teach for America, and we highlight the need for additional research on the growing cadre of teachers entering the teaching profession through alternative routes, and subsequently influencing policymaking processes.